Estimation of Total Blood Volume and its Correlation with Different Parameters for Expressing Blood Volume in Normal Subjects - Haq, Ihtesham ul (Journal of Postgraduate Medical Institute, 2011)
Blood volume was measured on 25 normal adult subjects by using chromium 51 as tracer element and was then statistically correlated with different parameters i-e height, weight and surface area for expressing blood volume. High significant correlation between blood volume and surface area in male (R=0.9, P<0.00) and female subjects (R=0.06, P<0.00) was found. It is concluded that surface area should be used for expressing blood volume as a reliable parameters.